Reevaluation of species richness in Winnertzia (Diptera, Cecidomyiidae, Winnertziinae), with descriptions of 37 new species from Sweden, Peru and Australia - Jaschhof, Mathias; Jaschhof, Catrin (Zootaxa, 2020)
Tentative studies of Malaise trap samples from different geographic regions and habitats indicate unanimously that Winnertzia, a genus of mycophagous gall midges (Cecidomyiidae), is exceptionally speciose, but hard data in proof of that were previously unavailable. A taxonomic inventory of mycophagous cecidomyiids in Sweden has now revealed that, of 751 species found in total, 93 are Winnertzia. A preliminary census in 2013 had identified only 26 different Winnertzia in Sweden. Two factors are responsible for this increment: the inclusion of large amounts of fresh material to study and the application of a narrower species concept. The latter results from the reevaluation of male morphological characters in the light of COI sequence (DNA barcoding) data. With the inclusion of 37 new Winnertzia described here, the genus now contains 136 extant species. New Winnertzia discovered in Sweden are described here under the following names: W. acutistylus sp. nov., W. angustistylus sp. nov., W. arctostylus sp. nov., W. bicolor sp. nov., W. brachytarsus sp. nov., W. dentata sp. nov., W. egregia sp. nov., W. ekdalensis sp. nov., W. fraxinophila sp. nov., W. grytsjoenensis sp. nov., W. hamatula sp. nov., W. hemisphaerica sp. nov., W. imbecilla sp. nov., W. incisa sp. nov., W. inornata sp. nov., W. lapponica sp. nov., W. lobata sp. nov., W. longicoxa sp. nov., W. normalis sp. nov., W. oelandica sp. nov., W. ombergensis sp. nov., W. parvidens sp. nov., W. pilosistylus sp. nov., W. pratensis sp. nov., W. pustulatula sp. nov., W. quercinophila sp. nov., W. rickebasta sp. nov., W. ruliki sp. nov., W. serri sp. nov., W. setosa sp. nov., W. silvestris sp. nov., W. smalandensis sp. nov., W. sundini sp. nov., W. tumidoides sp. nov., and W. upplandensis sp. nov. Additionally, W. panguana sp. nov. is the first Winnertzia described from the Neotropical region (Peru), and W. warraensis sp. nov. is the first member of the genus described from the Australasian region (Tasmania). Parwinnertzia Felt, 1920 syn. nov. is revealed to be a junior synonym of Winnertzia Rondani, 1860, implying the recombinations of Winnertzia notmani (Felt) comb. nov. and Winnertzia italiana (Mamaev & Zaitzev) comb. nov. The intrageneric classification of Winnertzia is reviewed and developed further, with the W. setosa group introduced for species whose gonostylar claw is conspicuously long and exposed, and whose gonocoxal emargination is bordered by dense, large setae. Winnertzia feralis Mamaev, revived here from synonymy with W. tridens Panelius, and W. fusca Kieffer are new faunistic records in Sweden. Swedish records published in the past of W. brachypalpa Mamaev and W. pravdini Mamaeva & Mamaev rest on misidentifications, and both species are deleted from the Swedish checklist.